Recurrent pulmonary aspergillosis and mycobacterial infection in an unsplenectomized patient with type 1 Gaucher disease. (March 2014) - Machaczka, Maciej; Lorenz, Fryderyk; Kleinotiene, Grazina; Bulanda, Agnieszka; Markuszewska-Kuczyńska, Alicja; Raistenskis, Juozas; Klimkowska, Monika
Abstract Background. The clinical presentation of Gaucher disease (GD), an inherited lysosomal storage disorder caused by the deficient activity of the lysosomal enzyme glucocerebrosidase, is highly variable, and three clinical types are distinguished based upon the presence of neurologic symptoms. Thrombocytopenia, anemia, hepatosplenomegaly, and bone manifestations are the most typical signs of GD type 1 (GD1). Case presentation. We present the case of an unsplenectomized man suffering from heterozygous GD1 with mutations of c.1226A>G (N370S) and RecNci I (L444P, A456P, and V460V) in the GBA1 gene, who developed recurrent pulmonary aspergillosis caused by Aspergillus fumigatus and a mycobacterial infection caused by Mycobacterium avium. Despite long-lasting therapy of both aspergillosis (including antifungal drugs and surgery), and the mycobacterial infection (triple therapy with rifampicin, ethambutol, and clarithromycin), recurrent positivity for M. avium and A. fumigatus was detected. Conclusions. Symptomatic lung involvement and an increased susceptibility to pulmonary infections are uncommon in GD and, if present, are often associated with more severe disease manifestations. To our knowledge, this is the first published report on the association of GD and pulmonary aspergillosis and mycobacterial infection. It illustrates the increased susceptibility of untreated GD patients to opportunistic pulmonary infections and ineffective eradication of these infections despite adequate therapy.